Mutational and Immunophenotypic Profiling of a Series of 8 Tubo-ovarian Carcinosarcomas Revealed a Monoclonal Origin of the Disease. (July 2020) - Trento, Mariangela; Munari, Giada; Carraro, Valentina; Lanza, Cristiano; Salmaso, Roberta; Pizzi, Sara; Santoro, Luisa; Chiarelli, Silvia; Dal Santo, Luca; Nardelli, Giovanni B.; Saccardi, Carlo; Nicoletto, Ornella; et al.
Abstract : Carcinosarcomas are rare, highly aggressive neoplasms composed of a combination of carcinomatous and sarcomatous elements. These tumors represent a paradigmatic field for the study of intratumor heterogeneity. A series of 8 tubo-ovarian carcinosarcomas was characterized for the following: (i) immunohistochemical expression of MNF116, epithelial membrane antigen, vimentin, S100, chromogranin, synaptophysin, desmin, myogenin (MYF4), and p53; (ii) mutational profiling of KRAS, BRAF, PIK3CA, NRAS, TP53, and DICER1 genes. Heterologous differentiation was present in 6 of 8 tumors. Cytokeratin MNF116 and epithelial membrane antigen were positive in all the carcinomatous components and in 87.5% and 50.0% of the sarcomatous components, respectively. The sarcomatous components showed positive staining for vimentin in all cases. Two cases demonstrated positivity for neuroendocrine markers in their carcinomatous components. All rhabdomyosarcomas were positive for desmin and MYF-4. Chondrosarcomas were positive for S100. All but one tumor showed similar p53 immunoreactivity in both the carcinomatous and sarcomatous components, and one case showed cytoplasmic p53 expression. Three of 8 cases (37.5%) showed TP53 mutations, and, in 2 cases, the TP53 mutation was shared by both epithelial and mesenchymal components. DICER1 mutation was found in all components of one case. Mutations in KRAS, NRAS, BRAF, and PIK3CA genes were not found in the study cohort. Our results highlight the heterogeneity of ovarian carcinosarcomas at the phenotypic level. A common mutational signature was observed in both components in 3 of 4 informative tumors. More studies are required to dissect different levels of ovarian carcinosarcomas' heterogeneity in order to define the best therapeutic approaches to these aggressive neoplasms.